2018
DOI: 10.1108/ijmhsc-06-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

The integration of immigrant nurses at the workplace in Malta: a case study

Abstract: Purpose The purpose of this paper is to identify the extent to which immigrant nurses have integrated within the Maltese healthcare system. Design/methodology/approach This research consisted of a qualitative case study approach which was conducted within Malta’s four public entities in the secondary care sector. In this case study, data were collected through 34 semi-structured interviews with ten nursing managers, 12 Maltese nurses and 12 immigrant nurses. The data were analysed using content analysis. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
(52 reference statements)
2
16
0
Order By: Relevance
“…We recommend that management of health care institution provide and facilitate guidance to promote and foster good work relations, power equity, and respectful treatment for not only the newcomers, but for all HCPs. The findings in our study confirm the outcomes of previous studies that argue that adequate support of management is important to make workforce integration a truly two-way process (Buttigieg et al, 2018;Kuokkanen et al, 2016;Ramji & Etowa, 2018). In light of our results, two directions for future research can be identified.…”
Section: Implication For Practicesupporting
confidence: 89%
See 1 more Smart Citation
“…We recommend that management of health care institution provide and facilitate guidance to promote and foster good work relations, power equity, and respectful treatment for not only the newcomers, but for all HCPs. The findings in our study confirm the outcomes of previous studies that argue that adequate support of management is important to make workforce integration a truly two-way process (Buttigieg et al, 2018;Kuokkanen et al, 2016;Ramji & Etowa, 2018). In light of our results, two directions for future research can be identified.…”
Section: Implication For Practicesupporting
confidence: 89%
“…Cultural clashes with colleagues were widely reported. The host colleagues had not been able to bridge the gap between different work cultures either (Buttigieg, Agius, Pace, & Cassar, 2018;Maltby, de Vries-Erich, & Lund, 2016;Putturaj & Prashanth, 2017;Steinmann, 2019;Wachter & Fleischmann, 2018). Intercultural understanding, egalitarianism principles, and positive interactions between immigrant nurses and established nurses are factors which influence positive workforce integration.…”
Section: Processes Of Workforce Integrationmentioning
confidence: 99%
“…However, language barrier is an added challenge that has received less attention within the context of hydration in the older population. This is a highly significant issue in Malta, in view of the high mobility of nurses and care staff from overseas (Buttigieg et al 2018), in response to the rapid growth of the health sector. Buttigieg et al (2018) identified language barrier between immigrant nurses and Maltese patients who were only fluent in their native language, as one of the commonest issues.…”
Section: Discussionmentioning
confidence: 99%
“…The EPA is a government-led program, so it should explain the need to introduce foreign nurses into Japan in intelligible terms. Currently, the MHLW states that "introducing foreign nurses is not to combat the shortage of nurses in Japan, but to respond to the request of the partner countries to accept the nurses" [24]. The statement is not helpful in persuading hospitals with nurse shortages, especially in rural regions [25].…”
Section: Discussionmentioning
confidence: 99%